Alpha 1 antitrypsin serum levels and phenotypes in patients with retinal vasculitis. Issue 7 (July 1985) - Wakefield, D; Easter, J; Breit, S N; Clark, P; Penny, R
Abstract : alpha 1 antitrypsin is an important immunoregulatory protein, the serum level of which is genetically determined. Deficient phenotypes of this ubiquitous protease inhibitor are associated with a variety of inflammatory diseases including anterior uveitis. In order to investigate the role of this protease inhibitor in the pathogenesis of retinal vasculitis (RV) 25 patients were investigated. Diseases associated with RV included Behcet's syndrome (8), SLE (2), and sarcoidosis (1). Deficient phenotypes of alpha 1 antitrypsin were not associated with RV. However, the serum alpha 1 antitrypsin level was significantly increased in patients with active RV and paralleled disease activity in patients studied prospectively.